Development of the petaloid bracts of a paleoherb species, Saururus chinensis. - Yin-He Zhao (Public Library of Science (PLoS), 2021)
Saururus chinensis is a core member of Saururaceae, an ancient, perianthless (lacking petals or sepals) family of the magnoliids in the Mesangiospermae, which is important for understanding the origin and evolution of early flowers due to its unusual floral composition and petaloid bracts. To compare their transcriptomes, RNA-seq abundance analysis identified 43,463 genes that were found to be differentially expressed in S. chinensis bracts. Of these, 5,797 showed significant differential expression, of which 1,770 were up-regulated and 4,027 down-regulated in green compared to white bracts. The expression profiles were also compared using cDNA microarrays, which identified 166 additional differentially expressed genes. Subsequently, qRT-PCR was used to verify and extend the cDNA microarray results, showing that the A and B class MADS-box genes were up-regulated in the white bracts. Phylogenetic analysis was performed on putative S. chinensis A and B-class of MADS-box genes to infer evolutionary relationships within the A and B-class of MADS-box gene family. In addition, nature selection and protein interactions of B class MADS-box proteins were inferred that B-class genes free from evolutionary pressures. The results indicate that petaloid bracts display anatomical and gene expression features normally associated with petals, as found in petaloid bracts of other species, and support an evolutionarily conserved developmental program for petaloid bracts.